2006
DOI: 10.1159/000098320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diabetes Mellitus, Chronic Renal Failure and Hemodialysis on Serum and Salivary Antioxidant Status

Abstract: Aim: To analyze various oxidative stress parameters in the saliva and serum of patients with chronic renal failure (CRF) and/or diabetes mellitus (DM), and to compare them in dialytic vs. pre-dialytic patients. Method: 50 consenting patients were divided into five subgroups of patients: severe CRF (dialytic) without DM, severe CRF (dialytic) with DM, mild CRF (pre-dialytic) without DM, mild CRF (pre-dialytic) with DM, and with DM but without CRF (controls). Uric acid (UA), peroxidase and total antioxidant stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Recently, Ben‐Zvi et al 32 studied uric acid, peroxidase, and total antioxidant status in saliva and serum in chronic renal failure and patients with DM. They reported that DM increased the oxidative stress burden in serum and saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ben‐Zvi et al 32 studied uric acid, peroxidase, and total antioxidant status in saliva and serum in chronic renal failure and patients with DM. They reported that DM increased the oxidative stress burden in serum and saliva.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that salivary UA is a suitable marker for qualitatively evaluating dialysis efficacy, given that patients experiencing renal failure have high plasma and salivary UA concentrations (19) that are significantly decreased by dialysis (8, 9, 20). Goll and Mookerjee also observed that UA and creatinine concentrations in whole saliva correlated significantly with those in serum and speculated that a saliva diagnostic test would be useful for reducing the number of blood tests for anemic and pediatric patients with renal disease (6).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the compositional changes in saliva produced by dialysis (8, 9), but the present investigation is the first to offer a method for simultaneously monitoring 2 salivary analytes for qualitatively assessing dialysis efficacy. It is important to note that in some cases a single analyte does not change while the second analyte shows a decrease consistent with the clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired radical scavenger function has been linked to the decreased activity of enzymatic and non-enzymatic scavengers. In particular, the action of superoxide dismutase (SOD), glutathione peroxidase (GSH-PX) and catalase (CAT), enzymes involved in the detoxification of H 2 O 2 , has been observed in chronic diabetes (Ben-Zvi et al, 2007). Increasing concentrations of lipid peroxidation by products, indicative of oxidative damage, have been observed in the cerebral microvasculature and brain tissue of diabetic rats (Nishikawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%